2015
DOI: 10.1016/j.amjsurg.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

A cost analysis of a pancreatic cancer screening protocol in high-risk populations

Abstract: Background Pancreatic cancer is the 4th leading cause of cancer death in the U.S. A screening protocol is needed to catch early stage, resectable disease. This study suggests a protocol for high-risk individuals and assesses the cost in the context of the Affordable Care Act. Methods Medicare and national average pricing were used for cost analysis of a protocol using MRI/MRCP biannually in high-risk groups. Results: ‘ Costs per year of life added’ based on Medicare and national average costs, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 23 publications
0
34
0
2
Order By: Relevance
“…10.2217/fon-2016-0123 review Coronel & Waxman future science group 241 patients with solid pancreatic lesions showed that the use of immediate OCE does lead to fewer needle passes (OCE = 4 vs no OCE = 7; p < 0.0001), but does not improve the diagnostic yield of malignancy and proportion of specimen adequacy. In addition, the use of immediate OCE did not affect overall procedure time, adverse events rates, number of repeat procedures, cost and sample quality [37].…”
Section: • • Pancreatic Cystic Lesions and The Importance Of Endoscopymentioning
confidence: 94%
See 1 more Smart Citation
“…10.2217/fon-2016-0123 review Coronel & Waxman future science group 241 patients with solid pancreatic lesions showed that the use of immediate OCE does lead to fewer needle passes (OCE = 4 vs no OCE = 7; p < 0.0001), but does not improve the diagnostic yield of malignancy and proportion of specimen adequacy. In addition, the use of immediate OCE did not affect overall procedure time, adverse events rates, number of repeat procedures, cost and sample quality [37].…”
Section: • • Pancreatic Cystic Lesions and The Importance Of Endoscopymentioning
confidence: 94%
“…The relatively low incidence of pancreatic cancer make population-wide screening a nonviable option since it is unpractical and costly [7,8]. As such, there is ongoing research invested to identify at risk populations to apply cost-effective screening strategies [7,[9][10].…”
mentioning
confidence: 99%
“…Costs of screening protocols in individuals at risk for pancreatic cancer development have been examined and appears to be cost-effective [80]. Utilizing early detection programs through several institutions may define better the risk factors for pancreatic cancer along with initiating clinical trials for earlier intervention.…”
Section: Future Directionsmentioning
confidence: 99%
“…Additionally, the risk of rising costs without helpful results or benefits due to pancreatic cancer screening programs is possible [100]. Psychoanalytical aspects for participants in screening programs have been studied and show that the distribution of anxiety and depression are similar to those in the normal populations, although a third worry about cancer [101,102].…”
Section: Considerationmentioning
confidence: 99%
“…The costs of these screening programs are affordable with respect to MRI and MRCP for patients with higher risk of development of PDAC, and specialization is important for effectiveness [100,109]. Nevertheless, it is important to reform the guidelines for screening to be more cost effective [100]. …”
Section: Considerationmentioning
confidence: 99%